Sosialisasi Perilaku Hidup Bersih dan Sehat pada Siswa/i Tingkat Sekolah Dasar - Sukimin Sukimin; Irfan Abdillah; Ria Kurniasih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Awareness of the importance of cleanliness and health must be instilled from an early age. We can start getting used to living a clean and healthy life from small things such as getting used to washing hands before doing activities, especially before eating, brushing teeth after eating, and getting used to always maintaining cleanliness in the home and school environment such as throwing trash in its place. From these small things we can start to create a clean and healthy environment, and a good level of health to avoid various diseases. The purpose of this activity is to increase knowledge and awareness of the importance of a clean and healthy lifestyle for elementary school students at SDN Negeri 003 Teritip. The methods used in this activity are counseling and interactive actions involving students. The results of this work program activity increase students' understanding of living a clean and healthy life through the role of parents and teachers who guide them at home and at school. Students can also develop this clean and healthy lifestyle in various situations and wherever they are which will later have a major impact on the environment around us.